Clint Eastwood and his Performance in The Bridges Of Madison County as a Precursor to the New Masculinity: The Close-Up of Robert Kincaid in the Rain - Cantos Ceballos, Antonio (Cinémas, 2024)
This article aims to explain how Clint Eastwood constructs his main male character in his film The Bridges of MadisonCounty (1995), Robert Kincaid, as a clear precursor of the new masculinity and, therefore, how he enables the viewer to connect with him (and the story) on an emotional level. This feeling man is particularly visible in a memorable scene almost at the end of the film, in which the minimalist look of the character prevails, when, in the pouring rain, he walks towards Francesca (Meryl Streep), who is sitting and who remains seated, in her husband’s truck. This scene is one of the most daring of Eastwood’s career, as Kincaid is literally drenched in rain, emotionally drained and all glamour has definitely been washed out of his image. Applying the analytical method of a qualitative and interpretative nature to its analysis, this article will explain how, in order to achieve this fragility and sensitivity (culturally feminine attributes), Eastwood’s performance goes beyond the confines of the script to explore the realm of emotions as an effective way of giving richness and depth to the character, leading him inevitably to discover what he really feels for someone, in this case his beloved Francesca.